Performance of Regression-Based Norms for Cognitive Functioning of Persons With Multiple Sclerosis in an Independent Sample - Marrie, Ruth Ann; Whitehouse, Christiane E.; Patel, Ronak; Figley, Chase R.; Kornelsen, Jennifer; Bolton, James M.; Graff, Lesley A.; Mazerolle, Erin L.; Marriott, James J.; Bernstein, Charles N.; Fisk, John D. (Frontiers in Neurology, 2021)
Background: Cognitive impairment is common in multiple sclerosis (MS). Normative data are used to interpret neuropsychological tests. Canadian regression-based norms have been developed for for tests included in BICAMS. Generalizability of these norms is essential for application in clinical and research settings. Objectives: We tested the performance of published Canadian regression-based norms in independently collected samples of Canadian healthy controls; and compared the ability of Canadian and non-Canadian regression-based norms to discriminate between healthy controls and persons with MS. Methods: We included two adult samples (first: 93 MS, 96 healthy; second: 104 MS, 39 healthy). Each participant was administered the oral Symbol Digit Modalities Test (SDMT), the California Verbal Learning Test (CVLT-II), and the Brief Visuospatial Memory Test-Revised (BVMT-R). Using healthy control data, we developed regression-based norms incorporating age, education and sex. We applied existing discrete and regression-based norms for the cognitive tests to healthy controls, and generated z-scores which were compared using Spearman rank and concordance coefficients. We compared the ability of each set of norms to discriminate between participants with and without MS using receiver operating characteristic curves. Within MS samples we compared the ability of various norms to discriminate between differing levels of disability and employment status using relative efficiency. Results: When we applied the published regression norms to our healthy samples, impairment classification rates often differed from expectations (7%). Most Spearman correlations between z-scores based on different published norms for the same cognitive test exceeded 0.90; concordance coefficients were lower. All norms for the SDMT discriminated between the MS and healthy control groups, but the CVLT-II and BVMT-R norms did not. Within the MS population, locally developed norms for the SDMT and CVLT-II had the highest relative efficiency to discriminate between disability levels or employment status. Conclusion: Our findings emphasize the value of local norms when interpreting the results of cognitive tests and demonstrate the need to consider and assess the performance of regression-based norms developed in other populations when applying them to local populations, even when they are from the same country. Development of regression-based norms should involve larger, more diverse samples to ensure generalizability.